PENGEMBANGAN LKPD BERBASIS PENDEKATAN DEEP LEARNING PADA MATERI SISTEM REPRODUKSI MANUSIA KELAS XI SMA - Maulina, Mailin; Darmadi; Yustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The topic of the human reproductive system for Grade XI senior high school students is considered difficult to understand due to its abstract nature, complex concepts, and extensive memorization requirements. In addition, the limited variety of teaching materials and the suboptimal implementation of Student Worksheets (LKPD) have resulted in students being less actively engaged and unable to achieve a deep understanding of the subject matter. Therefore, it is necessary to develop instructional materials that can support meaningful learning through the Deep Learning approach. This study aimed to develop and evaluate the quality of a Student Worksheet (LKPD) based on the Deep Learning approach for the topic of the human reproductive system for Grade XI senior high school students. The study employed a Research and Development (R&D) method using the ADDIE model, which was limited to the development stage. Data were collected through validation by four validators (two university lecturers and two biology teachers) and through limited trials involving 10 Biology Education students and 20 Grade XI senior high school students. The data were analyzed descriptively using a Likert scale. The results showed that the developed Deep Learning-based LKPD possessed excellent quality. The validation results obtained an average score of 3.66, categorized as highly valid. The first limited trial achieved an average score of 3.69, categorized as very good, while the second limited trial obtained an average score of 3.52, also categorized as very good. Overall, the LKPD achieved an average quality score of 3.62, classified as very good, indicating that it is suitable for use in the learning process.